Polyploidy and hybridization in the Mediterranean and neighbouring northern areas: examples from the genus Cardamine (Brassicaceae) - Marhold, Karol; Šlenker, Marek; Zozomová-Lihová, Judita (Biologia Serbica, 2018)
The genus Cardamine is distributed worldwide and is rich in polyploids. Here we review the considerable amount of knowledge accumulated on polyploid species and related diploids over the last twenty years, particularly in the Mediterranean area and neighbouring regions of Central Europe. These studies addressed the taxonomic treatment of polyploids, their origin and evolution, phylogenetic relationships to diploid and other polyploid relatives, and overall morphological, genetic, karyological and ecological patterns. The revealed parentage of polyploids such as C. asarifolia, C. flexuosa and C. ´schulzii shows the power of recently developed molecular and cytogenetic approaches, which enable us to understand how the polyploid taxa originated, became established and further evolved. It is emphasised that diploid-polyploid species complexes, such as the C. amara and C. pratensis groups, represent true natural laboratories for polyploid studies. Particularly the species complex of C. pratensis contains numerous diploid lineages and polyploid populations of all levels up to dodecaploids, including aneuploids and dysploids, providing excellent possibilities for the application of a wide spectrum of methodical approaches to understand the processes underlying polyploid evolution. Hybridization revealed in this genus occurs both at the homoploid and heteroploid levels and mainly in mountain regions, where parapatric and/or ecologically differentiated close relatives come into contact. These studies document that interspecific gene flow can result in various patterns, such as continuous variation in hybrid swarms (C. pratensis ´ C. raphanifolia), established hybrid species of significant evolutionary potential (C. ´schulzii, C. ´insueta), or largely sterile hybrids of first generations only and persistence through vegetative propagation (C. ×ferrarii, C. ´enriquei). All of these cases also show how recent hybridization and introgression add to the complexity of reticulated patterns of evolution in Cardamine in the Mediterranean and adjacent areas.